2021
DOI: 10.3390/jcm10204686
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Associated Choroidopathy

Abstract: The aim of the study is to report on the indocyanine green angiography (ICGA) and OCT findings in patients hospitalized for severe COVID infection. In this observational prospective monocentric cohort study, we included patients hospitalized for severe COVID infection. The main outcomes were ICGA and OCT findings. A total of 14 patients with a mean age of 58.2 ± 11.4 years and a male predominance (9/14 patients; 64%) were included. The main ICGA findings included hypofluorescent spots in 19 eyes (68%), intervo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In COVID-19, dark spots showing hypoperfusion in the choriocapillaris have been detected in OCT angiography. This finding was especially detected in patients with high D-dimer levels 33 . Therefore, D-dimer levels of COVID-19 patients are particularly important and there is a risk of pathological changes due to increased coagulation in tissues with high blood supply, such as the choroid.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In COVID-19, dark spots showing hypoperfusion in the choriocapillaris have been detected in OCT angiography. This finding was especially detected in patients with high D-dimer levels 33 . Therefore, D-dimer levels of COVID-19 patients are particularly important and there is a risk of pathological changes due to increased coagulation in tissues with high blood supply, such as the choroid.…”
Section: Discussionmentioning
confidence: 72%
“…In the study of Yaser et al, choroidal leakage and staining were detected in 71% of the patients in COVID-19. It has been reported that this leakage may be due to direct Sars-Cov2 damage in the glycocalyx 33 . In our study, ophthalmological examination findings were not included at the early period of covid disease due to risk of contagion and poor general health condition.…”
Section: Discussionmentioning
confidence: 98%
“…Systemic ocular manifestations of Covid-19 have been reported in numerous studies [4][5][6][7][8][9]. In contrast, the present study evaluated the role of steroid use in the development of these manifestations and also examined the effects of Covid-19 on ocular structures and choroidal thickness.…”
Section: Discussionmentioning
confidence: 87%
“…The cause of choroidal hypoperfusion may be secondary to SARS-CoV-2-induced damages, including direct viral-induced cell death, excessive inflammatory reactions accompanied by vascular inflammation and neutrophil infiltration. 13 Nonarteritic anterior ischemic optic neuropathy is caused by hypoperfusion of the optic nerve. Our patient presented with bilateral NAION in the setting of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Another finding which is in favor of NAION in this case is the presence of sever choroidal ischemia. The cause of choroidal hypoperfusion may be secondary to SARS‐CoV‐2‐induced damages, including direct viral‐induced cell death, excessive inflammatory reactions accompanied by vascular inflammation and neutrophil infiltration 13 …”
Section: Discussionmentioning
confidence: 99%